[2x ori (x-3) -2 ori (x-2) ori (x+1)] ori (x-3)-[(3x+2) ori (x-1) - 3 ori (x-2) ori (x+3)] ori (x-2)
Ajutati-ma va rog :3 Eu l-am rezolvat , dar vreau sa vad daca am facut bine deoarece e un joc o nota de 10 :)) .

1

Răspunsuri

2014-11-11T15:38:18+02:00
[2x*(x-3)-2*(x-2)*(x+1)]*(x-3)-[(3x+2)*(x-1)-3*(x-2)*(x+3)]*(x-2)=
[2x^2-6x-2x+4*(x+1)]*(x-3)-[3x^2-3x+2x-2-3x+6*(x+3)]*(x-2)=
[2x^2-8x+4x+4]*(x-3)-[3x^2-1x-2-3x+6x+18]*(x-2)=
(2x^2-4x+4)*(x-3)-(3x^2+2x+16)*(x-2)=
2x^3-6x^2-4x^2+12x+4x-12-(3x^3+6x^2+2x^2-4x+16x-32)=
2x^3-10x^2+16x-12-3x^3-6x^2-2x^2+4x-16x+32=
2x^3-10x^2+16x-12-3x^3-8x^2-12x+32=
-x^3-18x^2+4x+20

^ inseamna la puterea a....